2013
DOI: 10.1074/jbc.m113.463695
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the CYK-4 Subunit of the Centralspindlin Complex Induces a Large Scale Conformational Change in the Kinesin Subunit

Abstract: Background: Cytokinesis requires formation of the centralspindlin complex. Results: The neck linker regions in ZEN-4 are highly mobile when free, but their mobility is greatly restricted by CYK-4 binding. Conclusion: Central spindle assembly requires a binding event that modulates the structure of the kinesin ZEN-4. Significance: Structural changes in the centralspindlin complex contribute to cell division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 43 publications
7
24
1
Order By: Relevance
“…As homo-FRET reflects the intra-molecular geometry of the two Venus moieties, this indicates that C120 binding changes the relative positioning of the two Venus moieties in a dimer. This is consistent with a report by electron paramagnetic resonance [ 24 ] and confirms that the effect of CYK-4 on the configuration of the ZEN-4 motor domains observed by HS-AFM also occurs in solution. Because the ZEN-4 construct used for this analysis did not contain the motor domain, we conclude that CYK-4 changes the structure of the neck domain of the ZEN-4 dimer.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As homo-FRET reflects the intra-molecular geometry of the two Venus moieties, this indicates that C120 binding changes the relative positioning of the two Venus moieties in a dimer. This is consistent with a report by electron paramagnetic resonance [ 24 ] and confirms that the effect of CYK-4 on the configuration of the ZEN-4 motor domains observed by HS-AFM also occurs in solution. Because the ZEN-4 construct used for this analysis did not contain the motor domain, we conclude that CYK-4 changes the structure of the neck domain of the ZEN-4 dimer.…”
Section: Resultssupporting
confidence: 93%
“…Because of these unusual mechanistic features, the molecular structure of the heterotetrameric centralspindlin complex of CYK4 and MKLP1 is of great interest. Although a recent study using electron paramagnetic resonance spectroscopy reported a change in the mobility of ZEN-4 neck residues upon CYK-4 binding [ 24 ], it remains unclear how this influences the configuration of the two motor domains and how this modulates microtubule bundling by the complex.…”
Section: Introductionmentioning
confidence: 99%
“…Since previous studies had shown that Tum works as a molecular switch which activates the kinesin motor function of Pav (Davies et al, 2015; Tao et al, 2016; White et al, 2013), we examined whether the presence of Tum protein could affect the F-actin bundling and/or crosslinking activities of Pav. Bacterially-purified Tum protein alone does not bundle either F-actin or MTs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results do not rule out the possibility that a partner protein could bind to KIF7’s extended neck linker to alter the effective length and/or structure in a manner that changes KIF7’s microtubule-based functions. This possibility was suggested by Davies et al [68] based on a) a comparison of kinesin motors with extended neck linkers and b) the finding that the extended neck linker of the kinesin-6 CeZen-4 serves as the binding site for the partner protein CeCyk-4 which alters Ce Zen-4 structure to slow motor velocity and enable microtubule bundling [68, 69]. Further support for this idea comes from work on Ce Zen-4’s homolog Dm Pav where binding of the Dm Tum partner enables multi-motor microtubule gliding activity [70].…”
Section: Discussionmentioning
confidence: 99%